Integrated Management of Downy Mildew of Yellow Sarson - Kumar, Sunil; Singh, R. B.; Shakywar, R. C. (International Journal of Bio-resource and Stress Management, 2023)
An experiment was conducted at Student’s Instructional Farm of Narendra Deva University of Agriculture and Technology, Kumarganj, Faizabad to find out the integrated management of downy mildew. Yellow sarson varieties/entries under test showed variable downy mildew disease response for both the years. NDYS 2018, showed least susceptibility followed by NDYS 132-2 during 2006-07, while in 2007-08, NDYS 115-1 proved most susceptible followed by NDYS 2. In general highest disease intensity was recorded in 20th October sown crop as compared to 30th and 10th November sown crop during both the years. Second date of sowing (30th October) showed lower downy mildew intensity of 26.98 and 29.77% during 2006-07 and 2007-08, respectively. However, higher test weight and seed yield (3.75 and 3.70 g and 1385.73 and 1356.98 kg ha-1) were noted in first date of sowing i.e., 20th October in respective years. In respect of varieties, YST 151 showed lower downy mildew intensity of 27.59 and 30.26% and higher test weight of 3.75 and 3.68 g and seed yield of 1391.88 and 1363.07 kg ha-1 as compared to NDYS 2. Companion 0.15% was found most effective in reducing the disease severity and enhancing the test weight and seed yield during the years of testing followed by Mancozeb 0.2%. Maximum downy mildew intensity and minimum test weight and seed yield were noted in control plot.